If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4w + 8w + -2 = 6 Reorder the terms: -2 + -4w + 8w = 6 Combine like terms: -4w + 8w = 4w -2 + 4w = 6 Solving -2 + 4w = 6 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4w = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4w = 6 + 2 4w = 6 + 2 Combine like terms: 6 + 2 = 8 4w = 8 Divide each side by '4'. w = 2 Simplifying w = 2
| 2b+8=b+5 | | xc=l-gy | | 3+4q=8+3q | | -18=2(x-6) | | x-9=1.89 | | 200x+16000=600x | | (3+2i)+(-7+5i)= | | cx=l-Gy | | 7m^2-6m=0 | | z^2+625=0 | | 5n=5z-q | | 4x+4=-4y | | 29=log(x+5) | | 8x-9=5+3 | | n^2+4n-18=-6 | | 3n+30=9n | | 10-39=-log(x+5) | | 4(2a-8)=1(49a+70) | | 3x^2-28x+51=0 | | 16=21-logx | | (2x-11)(2x-11)-16(4x-10)=38-5*x*x | | 10=39-log(x+5) | | 55+3x+2=13x-3 | | a+5=37 | | 3x=144 | | 2x^2=y | | 6p+5t=-16 | | 17x^2-4x+2=0 | | y=5+3x+2x^2 | | -x^2+4-3=3x-7 | | y=2x^2+3x+5 | | 104-7x=20x+20 |